Pengaruh Variasi Komposisi Elektroda E7016 Terhadap Hasil Pengelasan Shield Metal Arc Welding Butt Joint Material Baja SS 400 Dengan Analisa Komparatif - Zaira, Jupri Yanda; Bennafi El Hasani, Oqbah; Ma’a , Mustaza; Akhyan, Amnur (Politeknik Caltex Riau, 2024)
Welding is a technique for joining metals by melting a portion of the base metal and filler metal, with or without additional metal, to produce a continuous metal joint. The aim of this research is to determine the effect of electrode composition from three brands, namely Niko Steel, Atlantic, and Kobelco, on tensile strength, bending, and impact. This study uses SMAW welding with a single V butt joint in the 1G/PA position on SS 400 steel plates, using 4.0 mm diameter electrodes. The welding results are then inspected visually and with a NDT penetrant test to ensure conformity with TWI acceptance standards. Subsequently, the workpieces are cut with a bandsaw into specimens according to ASTM E8 for tensile testing, ASTM E290 for bending testing, and ASTM E23 for impact testing. The research results show that the highest tensile test value is achieved with Niko Steel electrodes, having an average tensile strength of 792.5 MPa. In bending tests, the highest bending strength is also observed with Niko Steel electrodes, averaging 8.71kN. In impact testing, the highest average value is found with Niko Steel electrodes, at 1.1 J/mm².